Kadar Protein Dan Kualitas Tempe Koro Pedang Dengan Penambahan Bekatul Dan Konsentrasi Ragi Tempe Yang Berbeda - Ambarwati, Erviyan Tri; , Dra. Titik Suryani M.Sc (2016)
Innovations making tempe "koro pedang" with the addition of rice bran and yeast tempe to increase the nutrient content in soybean. The purpose of this study to determine the levels of soluble protein and quality tempe "koro pedang" with the addition of rice bran and concentration yeast tempe different. Reasearch methods with completely randomized design with two factors, one is the composition "koro pedaang" : rice bran (A1 = "koro pedang" 200 g, A2 = "koro pedang" 180 g : rice bran 20 g, A3 = "koro pedang" 170 g : rice bran 30 g, lentils sword A4 = "koro pedang" 160 g : rice bran 40 g) and the second factor is the concentration of yeast tempe (B1 = 0.1%, B2 =0.2% and B3 = 0.3%) with 12 treatment. The results showed that the rice bran and Rhizopus sp. Different can affect the levels of soluble protein tempeh canavalia. The highest levels of soluble protein tempe "koro pedang" on sword tempe treatment by comparison "koro pedang" 160 g : rice bran 40 g and yeast tempe 0,1% (A4B1) that is equal to 8.7 g/L. Lowest levels of soluble protein in tempeh treatment with a "koro pedang" ratio of "koro pedang" 200 g and the concentration of yeast tempe 0,3% (A1B3) is 3.95 g / L.